An Analysis of Lexical Error in the Descriptive Text Writing Produced by the Eighth Grade Students of MTs. Wahid Hasyim Kunir - Ilma Atisyatur Rochmaniyah; Bambang Suharjito; Made Adi Andayani T (Pendidikan Fisika FKIP UNEJ, 2017)
Abstract: This research was intended to investigate the lexical errors types, to calculate the percentage and to analyze the causes of each lexical error type found in the descriptive text writing produced by the eighth grade students of MTs. Wahid Hasyim Kunir. The area determination method of this research was conducted by using purposive method. The subjects were the eighth grade students at MTs. Wahid Hasyim Kunir in the 2015/2016 academic year. The data of this research were obtained from 30 students' descriptive writing test. The analysis of the data was based on Llach’s lexical errors taxonomy (2011) which divides lexical error types based on the sources of errors and major types of error. The study found a total of 86 lexical errors in five types of lexical error. Misspelling was the most common lexical error with a total of 26 errors and the percentage is 30.23%. It happened because the students were influenced by intralingual transfer. The results of this study confirm that almost all of the students have a serious problem in determining the correct spelling of lexical items in the target language. Hence, this study suggests that vocabulary teaching and learning in English as a Second Language (ESL) or English as a Foreign Language (EFL) contexts and error correction during the teaching-learning process may become alternative ways to help in minimalizing the number of lexical errors in students’ writing.Keywords: lexical errors, writing, descriptive text.